2013
DOI: 10.1007/s00296-013-2750-z
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid-induced neuropsychiatric disorders: review and contrast with neuropsychiatric lupus

Abstract: The aim of this review is to analyze the available literature regarding the neuropsychiatric (NP) disturbances associated with corticosteroid (CS) therapy; to determine the nature, severity, and frequency of these NP symptoms; and to identify the various risk factors involved in the development of CS-induced NP disturbances. We searched the available literature since the advent of corticosteroid therapy (1950) utilizing the PubMed database ( www.pubmed.gov). Primary articles were identified, and they and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 80 publications
1
67
0
6
Order By: Relevance
“…cognitive deficits in SLE patients. [8][9][10][11][12][13][14] To the best of our knowledge, only one study has identified corticosteroid use as a factor associated with cognitive impairment in SLE.…”
Section: -3mentioning
confidence: 99%
“…cognitive deficits in SLE patients. [8][9][10][11][12][13][14] To the best of our knowledge, only one study has identified corticosteroid use as a factor associated with cognitive impairment in SLE.…”
Section: -3mentioning
confidence: 99%
“…This predisposition can be important in the emergence of the clinical condition, including corticosteroid use, intrusive infection, and neuropsychiatric response, depending on SLE. Thus, SLE contains the highest risk of psychiatric disorder triggered by corticosteroid (9). The distinction of psychiatric conditions stimulated by steroid from neuropsychiatric SLE (NPSLE) is usually difficult (9).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, SLE contains the highest risk of psychiatric disorder triggered by corticosteroid (9). The distinction of psychiatric conditions stimulated by steroid from neuropsychiatric SLE (NPSLE) is usually difficult (9). Manic term development in SLE is generally thought to be associated with corticosteroid use (7,9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations